A comparison between forensic observation patients admitted with first episode mental illness and those with an existing mental illness - Ramouthar, Reyanta (My University, 2016)
Introduction Psychiatric illness combined with criminal offending is an area that remains poorly understood. There is a perception of an increased association between psychiatric illness and criminal offending. Objectives The study aimed to compare the demographic and clinical profiles of individuals referred for forensic observation with first episode mental illness, to those with an existing mental illness. In addition, a comparison of these two groups with regards to the nature of the offence, type of offence, and outcome of the observation period, was conducted. Substance Use Disorders were specifically assessed. Methods All forensic observandi above 18 years, admitted to Sterkfontein Psychiatric Hospital between January 2011 and December 2012 with a positive finding of a psychiatric diagnosis at the end of the observation period, were included. The demographic and clinical profile, as well as the nature of the offence, type of offence, and outcome of the observation period, were obtained from the hospital records for each individual. This information was then assigned into two groups according to first episode or existing mental illness. A comparison was then piloted between these groups. Results Overall the sample included 436 observandi; 177 were in the first episode group and 259 were in the existing mental illness group. The principal findings from the study included associations between first episode mental illness, and existing mental illness, with criminal offending. The majority of the offenders were male, and they were either single, divorced, widowed or separated. Most of the observandi were between 25 and 35 years old. Overall the most common diagnosis was a Substance Use Disorder, followed by Schizophrenia, Intellectual Disability and Bipolar Disorder. The most common violent offences included sexual offences, assault with intent to cause grievous bodily harm, murder, and malicious damage to property, whilst the most common non-violent offence was theft. The majority of the sample was recommended for admission as state patients and involuntary mental health care users. For the remainder of the sample, trial was to proceed. Conclusion Future research in forensic psychiatry is recommended to assist our understanding of these individuals, so that we can help to reduce the incidence of criminal offending in patients with mental illness.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree Of Master of Medicine in the branch of Psychiatry. Johannesburg 2015